Experimental study of multiphase flow in porous media during CO2 geo‐sequestration processes - Saeedi, Ali (Curtin University, 2011)
A range of variable factors are expected to influence multiphase flow during CO2 geological sequestration. In order to investigate the effects of a number of these factors, a range of core-flooding experiments was carried out. Those factors which were expected to strongly influence the multiphase flow characteristics of the rock-fluids system during CO2 geo-sequestration, including cyclic CO2-brine flooding, flow direction, change in the reservoir net effective pressure and existence of residual natural gas saturation, were investigated.